1994
DOI: 10.1111/j.1600-0838.1994.tb00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported obstructive airway symptoms are common in young cross‐country skiers

Abstract: The reported high use of anti‐asthmatic drugs in cross‐country skiers prompted a study to assess the prevalence of self‐reported asthma, asthma‐associated symptoms and the use of anti‐asthmatic medication among cross‐country skiers. A self‐administered questionnaire based on the Medical Research Council questionnaire was answered by cross‐country skiers in the Swedish national ski team, in upper secondary school ski‐classes and in the Swedish army (n=305). Controls (n=141) were pupils from regular classes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
4

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 12 publications
1
22
4
Order By: Relevance
“…Our results contrast with other studies reporting a high prevalence of asthma among athletes in the United Kingdom, United States and Scandinavian countries (Dickinson et al, 2005;Larsson et al, 1993;Larsson et al, 1994;Leuppi et al, 1998;Weiler et al, 1998). The different results are probably due to the fact that these studies were conducted on elite athletes, such as those taking part in the Olympic Games (Dickinson et al, 2005;Maiolo et al, 2004;Weiler et al, 1998;Weiler & Ryan, 2000).…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Our results contrast with other studies reporting a high prevalence of asthma among athletes in the United Kingdom, United States and Scandinavian countries (Dickinson et al, 2005;Larsson et al, 1993;Larsson et al, 1994;Leuppi et al, 1998;Weiler et al, 1998). The different results are probably due to the fact that these studies were conducted on elite athletes, such as those taking part in the Olympic Games (Dickinson et al, 2005;Maiolo et al, 2004;Weiler et al, 1998;Weiler & Ryan, 2000).…”
Section: Discussioncontrasting
confidence: 85%
“…In apparent contrast with our findings, studies published in the last few years have demonstrated a high prevalence of self-reported asthma in elite athletes exercising in a cold environment (Larsson et al, 1993;Larsson et al, 1994;Leuppi et al, 1998). We hypothesise that strenuous training with inhalation of a high volume of air in competitive athletes may increase the asthma risk, differently from lower intensity exercise in amateurs.…”
Section: Discussioncontrasting
confidence: 85%
“…39 Finally, a possibly related phenomenon is the induction of an asthmalike syndrome in high-performance skiers, which has been confirmed by various groups in Scandinavia and has been associated with airways inflammation and the duration of exposure to subfreezing, windy conditions. [40][41][42] It would be interesting to know whether the individuals who developed this syndrome had a history of nasal sensitivity to CDA. In dogs, repetitive exposure of peripheral airways to CDA generates eosinophil, mast cell, and neutrophil influx and leads to thickening of the lamina propria, but it is not known whether these changes are associated with the magnitude of epithelial shedding induced by CDA.…”
Section: Discussionmentioning
confidence: 98%
“…Cross-sectional studies subsequent to this observation68 reported a higher prevalence of cough, wheeze, breathlessness and chest tightness on exercise in cross-country skiers than in non-athletic controls (figure 1). Importantly, the onset of symptoms is primarily in late adolescence and early adulthood8 and the prevalence of respiratory symptoms is higher in the adult than in the adolescent skier,6 7 In one study by Larsson, et al 6 50% of adult skiers had respiratory symptoms and airway hyper-responsiveness to methacholine and/or physician-diagnosed asthma. As airway hyper-responsiveness is also present in the winter and summer months, they suggested that strenuous training at low temperatures with the repeated inhalation of large amounts of cold air may be pathogenic factors for the development of asthma in athletes.…”
Section: Long-term Effectsmentioning
confidence: 90%